Absolutely Consistent Fiber-Optic Phase Synchronization Based On Fixed-Phase-Reference Optical Active Compensation - Rui Wu; Fei Yang; Yanguang Sun; Fang Wei; Youzhen Gui; Yaqian Ding; Haiwen Cai (IEEE Photonics Journal)
An absolutely consistent fiber-optic phase synchronization scheme based on fixed-phase-reference optical active compensation is proposed. By measuring the time interval of time pulse and the phase difference of frequency signal, and then using the optical delay line to compensate the phase change in real time according to a fixed phase reference, the phase period ambiguity and the phase-lock control initial randomness are eliminated, realizing a stable and repeatable fixed phase difference between different sites. Then the phase synchronization performances of stability and absolute consistence have been demonstrated through experiments in different scenarios. The phase difference fluctuation within 10000 s is only ±0.0006 rad, showing an ultra-high stability. Under the total of 5 different operations, including the signal source restart, system restart, adding 20 m additional fiber, adding 1 km additional fiber, and adding 2 km additional fiber, the maximum inconsistency of the mean phase difference is about 1% of one full cycle. The proposed and verified absolutely consistent phase synchronization method can well maintain the coherence in transferring frequency signal, having important application prospects in radar network and other time-frequency-phase synchronization-based coherent detection.